Experimental Analysis On Parameters Affecting The Material Removal Rate In Wire Electrical Discharge Turning Using The Taguchi Method - Raja Abdullah, Raja Izamshah; Mohd Zakaria, Muhammad Akmal; Kasim, Mohd Shahir; Mohamed, S.B. (IJENS Publisher, 2018)
Wire electrical discharge turning (WEDT) allows success in the machining of advanced materials, particularly for the cylindrical shape components used in the metrology, medical and aerospace field. Using WEDT technology, the micro dimension of geometrical features can be machined without constraints on difficult-to-machine electrically conductive materials. The high precision with large aspect ratio machining capability make WEDT valuable. The correct machining parameter selection is the most important aspect to take into consideration when machining by WEDT. Therefore, the purpose of this study was to rank, determine and optimise the machining parameters that affect the material removal rate (MRR) in WEDT process. As WEDT has as much as eleven control parameters in this study, representing a large number of machining, the Taguchi L-12 orthogonal array was used to obtain the required data with a minimum number of experiments. By using similar experimental data, the regression equation was developed to represent as fitness function for optimisation by genetic algorithm (GA). It was found that by selecting the fast feed of workpiece to machining zone, the faster material was removed and moreover, it dominated other machining parameters. The optimised parameters yield 1.398 mm³/min as the maximum value predicted for MRR recommended by GA.